NIR‐Emissive Chromium(0), Molybdenum(0), and Tungsten(0) Complexes in the Solid State at Room Temperature - Boden, Pit; Di Martino‐Fumo, Patrick; Bens, Tobias; Steiger, Sophie; Albold, Uta; Niedner‐Schatteburg, Gereon; Gerhards, Markus; Sarkar, Biprajit (Chemistry : a European journal, 2021)
The development of NIR emitters based on earth‐abundant elements is an important goal in contemporary science. We present here Cr(0), Mo(0), and W(0) carbonyl complexes with a pyridyl‐mesoionic carbene (MIC) based ligand. A detailed photophysical investigation shows that all the complexes exhibit dual emissions in the VIS and in the NIR region. The emissive excited states are assigned to two distinct triplet states by time‐resolved emission and step‐scan FTIR spectroscopy at variable temperature, supported by density functional theory. In particular, the NIR emissive triplet state exhibits unprecedented lifetimes of up to 600±10 ns and quantum yields reaching 1.7 ⋅ 10−4 at room temperature. These are the first examples of Cr(0), Mo(0) and W(0) complexes that emit in the NIR II region. This work presents emissive Cr(0), Mo(0), and W(0) complexes that contain a bidentate pyridyl‐mesoionic carbene ligand and CO coligands. These systems exhibit dual vis and NIR II emissions at room temperature. The emissive excited triplet states were characterized by temperature‐dependent luminescence and step‐san FTIR spectroscopy in combination with density functional theory. The NIR quantum yield increases from Cr(0) over Mo(0) to W(0), reaching a very high value of 1.4 ⋅ 10−3 at room temperature.